LEGAL CONSEQUENCES OF FORGERY IN SIGNATURES ON SALE AND PURCHASE DEEDS OF LAND RIGHTS (Case Study: Decision No. 58/Pdt.G/2020/PN Kwg) - Aulia, Salvia Nur; Rahmatiar, Yuniar; Abas, Muhamad (fakultas hukum universitas PGRI Semarang, 2024)
Purchasing and selling, giving, swapping, and other methods are some of the ways that land may be acquired. Buying and selling is a reciprocal arrangement wherein one party, the seller, agrees to transfer ownership rights to an object and the other, the buyer, agrees to pay a price that accounts for the difference between the two parties' respective ownership rights acquisition amounts. An official with the power to legitimately validate a sale and purchase, known as a Land Deed Making Officer (PPAT), must be present when the sale and purchase are finalized. The sale and purchase are legally binding acts, and the deed proves it. The validity of the land rights transfer depends on this. In judgment N0.58/Pdt.G/2020/PN Kwg, the judge considered a signature forgery in the sale and purchase deed. This study employs a descriptive analytical research type based on normative juridical research. In qualitative research, secondary data is gleaned via document studies. As a branch of the National Land Agency, PPAT has the status of a public official with the power to create genuine deeds pertaining to certain legal activities involving ownership rights to apartment buildings or land. that the land certificate's signature is a forger, which has legal ramifications since it falls short of the conditions for creating a Deed of Sale and Purchase and renders the document legally worthless.